A new nano-engineered hierarchical membrane for concurrent removal of surfactant and oil from oil-in-water nanoemulsion - Qin, Detao (2016)
Surfactant stabilized oil-in-water nanoemulsions pose a severe threat to both the environment and human health. Recent development of membrane filtration technology has enabled efficient oil removal from oil/water nanoemulsion, however, the concurrent removal of surfactant and oil remains unsolved because the existing filtration membranes still suffer from low surfactant removal rate and serious surfactant-induced fouling issue. In this study, to realize the concurrent removal of surfactant and oil from nanoemulsion, a novel hierarchically-structured membrane is designed with a nanostructured selective layer on top of a microstructured support layer. The physical and chemical properties of the overall membrane, including wettability, surface roughness, electric charge, thickness and structures, are delicately tailored through a nano-engineered fabrication process, that is, graphene oxide (GO) nanosheet assisted phase inversion coupled with surface functionalization. Compared with the membrane fabricated by conventional phase inversion, this novel membrane has four times higher water flux, significantly higher rejections of both oil (~99.9%) and surfactant (as high as 93.5%), and two thirds lower fouling ratio when treating surfactant stabilized oil-in-water nanoemulsion. Due to its excellent performances and facile fabrication process, this nano-engineered membrane is expected to have wide practical applications in the oil/water separation fields of environmental protection and water purification.